(untitled) (The Review of Diabetic Studies, 2024)
Existing processes for certifying and accrediting hospitals and other healthcare institutions were used to develop the simulation. But the Carnegie Foundation has also emphasized simulation as a useful teaching tool for nursing students. The training of student nurses presents a challenge to the advancement of nursing practice. The most important tool they bring to the clinical setting during their nursing profession is their education. As a result, the type of nurses they may become is reflected in their academic training. Nurses must be responsible for the results of their care in addition to having the necessary skills to deliver it effectively. This present study evaluates the scenario in terms of nursing students in selected hospitals of KSA. The study takes into account both the primary and secondary data. SPSS Ver. 22.0 was used to get the statistical results.